Industry 4.0: Challenges of Mechanical Engineering for Society and Industry - Muji Setiyo; Tuessi Ari Purnomo; Dori Yuvenda; Muhammad Kunta Biddinika; Nor Azwadi Che Sidik; Olusegun David Samuel; Aditya Kolakoti; Alper Calam (Universitas Muhammadiyah Magelang, 2021)
Today, in the industry 4.0 era, the boundaries of scientific disciplines are blurred, everything seems to be interrelated and shows the ability to be combined. Intelligent sensors combined with Artificial Intelligence (AI) have demonstrated their ability to influence processes, design, and maintenance in manufacturing systems. Mechanical engineering tasked with solving complex engineering problems must be able to adapt to this transformation, especially in the use of digital and IT to combine the principles of physics and engineering mathematics with materials science to design, analyze, manufacture, and maintain mechanical systems. On the other hand, mechanical engineering must also contribute to a better future life. Therefore, one of the keys to consistently playing a role is to think about sustainability, in order to provide benefits for society and industry, in any industrial era.